A 'tug of war' between more parks or better greenspace: The dilemma of meeting 'community expectations' with limited resources. (July 2022) - Boulton, Chris; Dedekorkut-Howes, Aysin; Byrne, Jason
Abstract: Rapid urbanisation is impacting availability of greenspace, regarded as a cornerstone of liveability in cities across the globe, presenting challenges for residents and governments alike. Scholars from fields as diverse as planning, engineering, health and psychology, are calling for more urban greenspace to remedy manifold urban challenges (e.g. stormwater attenuation, pollution reduction, health promotion and temperature modulation). Yet few have paused to question the viability of urban greenspace provision, especially its financial and administrative burdens for local government, nor whether simply providing more greenspace is efficacious. This paper investigates the perspectives of elected officials and local government officers towards greenspace provision in a rapidly growing Australian city: Logan, Queensland. Employing an in-depth case study including semi-structured interviews, public documents, and municipal and census data, the paper elucidates key factors that affect provision, highlighting the tension between supply and demand, and the role of planning practices. In determining greenspace provision, three clusters of factors are particularly instructive: (i) community expectations; (ii) governance tools; and (iii) financial resources. The findings point to a critical issue: providing urban greenspace cannot be simply reduced to a matter of inadequate resources - community expectations are a pivotal and often over-looked factor shaping urban greenspace provision. Graphical abstract: Unlabelled Image Highlights: The clamour for more greenspace could be setting local governments up for some serious future policy deficiencies Providing urban greenspace is more than supplying land and revenue for facility development Resourcing gaps arise when attempting to use existing resources optimally to achieve corporate objectives An effective approach to urban greenspace planning must adequately respond to the gaps in expectations and resources